Knowledge, Skills, and Attitude of Disaster Health Management Among Physiotherapists- A Scoping Review (International Journal of Physiotherapy, 2025)
Background: Disaster health management involves trauma, rehabilitation, and functional restoration, which are competencies of physiotherapists. On this, an increase in the incidences of natural and manmade disasters that, on average, are more severe calls for physiotherapists to have specific knowledge, abilities, and philosophy for health emergency intervention. Nevertheless, few studies focus on physiotherapists’ current disaster health management activities. In this study, physiotherapists' knowledge, skills, and attitudes in effective disaster health management will be evaluated, and recommendations will be made on the areas that need to be given attention in students learning disaster health management capacities.Methods: The literature review covered the currently available articles up to 2023 from 2010 focusing on knowledge, skills, and attitudes of physiotherapists in disaster health management and was registered with INPLASY with registration Number 2024110061. An extensive systematic search approach about the Peer-reviewed database like PubMed, Scopus, and PEDro was developed using keywords including “disaster health management”, “knowledge”, “skills”, “attitude”, “physiotherapist”, and “rehabilitation”. Scientific articles and recommendations published in English describing physiotherapists' general features and competencies in disaster situations were included. First, both titles and abstracts were checked for relevance; then, the full text of the articles in question was evaluated as relevant and of good quality. The demographic data and results on the physiotherapists’ knowledge, skills, and attitudes regarding disasters were analyzed using a qualitative approach.Results: Emergency readiness and curricular variation make physiotherapists often ill-prepared for disaster health management. Lack of adequate trauma and triage skills leads to reluctance to develop such skills because of inadequate motivation for disaster training, which is believed not to be very essential in daily practice.Conclusion: Improved, structured disaster drills for physiotherapists, such as disaster preparedness and trauma scenarios, could improve preparation. This study posited that integrating disaster management in physiotherapists’ routine education and promoting proactive disposition through simulations would enhance disaster preparedness and response and improve patient outcomes in disaster health management.